2007
DOI: 10.1111/j.1439-0523.2007.01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration through callus initiation from mature embryo of Triticum

Abstract: The behaviour of diverse Triticum genotypes in the tissue culture response of mature embryo callus was compared, and factors affecting tissue culture response were studied in this paper. Significant differences were detected in callus induction, embryogenic callus differentiation, plantlet regeneration and culture efficiency when mature embryos of 31 plants of different Triticum species were compared. These were the main wheat cultivars of the Chinese northern wintertype wheat region and breeding lines (Tritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Meanwhile, the current results prove that embryogenic callus formation and plant regenerability are also genotype-dependent. Similar results were found by Bi et al (2007). The hormone composition suitable for embryogenic callus formation and regeneration varies with genotypes, suggesting that the abilities of embryogenesis and regeneration for the callus derived from mature barley embryo may be dependent on not only hormone composition in the medium, but also on the hormone level in the callus.…”
Section: Discussionsupporting
confidence: 75%
“…Meanwhile, the current results prove that embryogenic callus formation and plant regenerability are also genotype-dependent. Similar results were found by Bi et al (2007). The hormone composition suitable for embryogenic callus formation and regeneration varies with genotypes, suggesting that the abilities of embryogenesis and regeneration for the callus derived from mature barley embryo may be dependent on not only hormone composition in the medium, but also on the hormone level in the callus.…”
Section: Discussionsupporting
confidence: 75%
“…Due to the relatively high frequency of embryogenic structure formation, T. diccocum 'Runo' had the highest culture efficiency of mature embryo tissues (3.41 plants/per initial explant). Generally speaking, this observation agrees with previous reports of Bi et al (2007), who found that the response of mature embryo-derived callus formation of T. diccocum was better than that of the other tetraploid (T. durum) and hexaploid (T. aestivum) wheats. On the other hand, in several other reports (Chauhan et al 2007, Chang et al 2012, Yang et al 2015) the difference between wheats with different genome composition (AABB vs. AABBDD) including T. diccocum was not clearly evident.…”
Section: о Alikina Et Alsupporting
confidence: 83%
“…Until recently, many wheat species were not analyzed for plant regeneration ability in vitro; but nowadays, the interest in such studies is on the rise (Chang et al 2012, Yang et al 2015, Özgen et al 2015. Over the years, several studies have demonstrated the possibility to regenerate plants from different tissues of tetraploid emmer wheat (AABB genome) (Eapen and Rao 1982, Chauhan et al 2007, Bi et al 2007, Chang et al 2012, Yang et al 2015, diploid T. monococcum and T. urartu (AA genome) (Eudes et al 2003, Yang et al 2015. Proliferation was induced in somatic cell cultures of tetraploid timopheevii wheat (AAGG genome) and hexaploid spelt wheat (AABBDD genome), although no shoot differentiation was observed (Lazar et al 1983) or the number of regenerated plants was low (Yang et al 2015(Yang et al , Özgen et al 2015.…”
Section: о Alikina Et Almentioning
confidence: 99%
See 2 more Smart Citations